Enhanced stability of CH3NH3PbBr3 quantum dots for electrochemiluminescence detection of saxitoxin - Yu Han; Ting Zhang; Rui Kang; Xin Gao; Jiawei Liu; Qingchun Yin; Hongmei Cao; Long Wu (Food Chemistry, 2026)

Evolution of lipid profiles, microbiota succession, and potential warmed-over flavor markers in prepared squid (Dosidicus gigas) during extended refrigerated storage: A multi-omics study - Xin Zhang; Rui Tan; Chengxin Lv; Zhiyuan Xiao; Kang Guo; Bin Zhang; Ru Song; Yan Xu; Wei Xia (Food Bioscience, 2026)

Transparent, bio-based dielectric films with ultrahigh breakdown strength fabricated from hydrogen-bonded cellulose acetate and tannic acid for energy storage - Rui Luo; Xin-rui Xiao; Zhe-hao Kang; Chao-qun Wu; Ting Huang; Nan Zhang; Yong Wang (Carbohydrate Polymers, 2026)

Mesoporous carbon nanospheres-confined ZnMn2O4/Mn3O4 heterostructures for sustainable zinc-ion storage - Ling-Xin Kong; Songtao Zhang; Yaxun Hu; Peng Liu; Wanchang Feng; Zefan Sang; Xiaotian Guo; Hao Gong; Rui Wang; Dae Joon Kang; Huan Pang (Chemical Engineering Journal, 2026)

Effect of the thickness of overlying soil on the location of trailing edge cracks in soil–bedrock landslides induced by water softening - Yun-kang Rao; Jia-xin Chang; Hai-ying Fu; Tao Yang; Huai-lin Chen; Zhe Zhang; Yi Yang; Rui Huang (Bulletin of Engineering Geology and the Environment, 2026)

Gallic acid-modified starch conjugates inhibit harmful aldehydes in fried battered fish: Based on structural characterization and antioxidant activity - Ying Li; Hao Zhang; Jiamu Kang; Meng Yang; Hanyu Liu; Wuyun Chen; Tingting Zhang; Deming Quan; Rui Zhang; Yuan Xia; Xin Du; Xiufang Xia (Food Research International, 2026)

Integrated metabolomics and transcriptomics analyses provide insights into flavor and color regulation during tomato postharvest ripening - Xian-Kang Xiao; Wei-Xin Liu; Xiao Lu; Cai-Rui Chen; Xin-Yi Zhang; Xiao-Jun Pu; Feng Wang (Postharvest Biology and Technology, 2026)

Exogenous melatonin alleviates heat stress-induced metabolic slowdown affecting broiler growth by improving lipid metabolism - Fei Song; Binglin Wang; Xin Kang; Aige Han; Huiyuan Rui; Xiangyang Xu; Yi Guo; Ming Ge; Xiaowen Jiang; Wenhui Yu (Journal of Thermal Biology, 2026)

Advancing the state of the art of cyclic direct simple shear Testing: Histories, current status, challenges and future trends - Xin Kang; Zi-Rui Ma; Louis Ge (Soil Dynamics and Earthquake Engineering, 2025)

Co-inoculation of Bacillus amyloliquefaciens and Pleurotus ostreatus alleviates replanting obstacles in continuously cropped soil by enhancing the soil nutrient cycle and beneficial microorganisms - Xue Luo; Man Xu; Xin-Li Yan; Rui Xing; Yi-Jin Kang; Hong-Wei Wang (Rhizosphere, 2025)

Selective separation and stepwise recovery of rare earth and aluminum from magnesium salt-based ionic rare earth leaching liquor - Xin Chen; Sihan Ouyang; Zhouyi Chai; Jianfeng Xu; Rui Kang; Yanfei Xiao; Zhifeng Xu (Journal of Environmental Chemical Engineering, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Effects of reversing the light-dark cycle on growth performance and intestinal health in heat-stressed broilers - Huiyuan Rui; Xiangyang Xu; Fei Song; Aige Han; Meiwei Lv; Xin Kang; Ming Ge; Xiaowen Jiang; Wenhui Yu (Journal of Thermal Biology, 2025)

Effortless rule: Effects of oversized microplastic management on lettuce growth and the dynamics of antibiotic resistance genes from fertilization to harvest - Jing-Yuan Chen; Lin-Jie Qin; Tiao Long; Rui-Ting Wu; Shi-Hua Niu; Shuo Liu; Wei-Kang Deng; Xin-Di Liao; Si-Cheng Xing (Journal of Hazardous Materials, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Rational design and pairing of single-domain antibodies for developing rapid detection methods for botulinum neurotoxins A and B - Ruomei Lv; Jiaxin Li; Xinyu Fang; Li Tang; Rui Shi; Jin Wang; Wenjing Zhang; Jinglin Wang; Guangyu Zhao; Jing Wang; Shan Gao; Xuefang Xu; et al. (Analytica Chimica Acta, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Association of prenatal multiple metal exposures with child neurodevelopment at 3 years of age: A prospective birth cohort study - Yun Qiu; Yuxin Liu; Ming Gan; Weiting Wang; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; Xin Xu; et al. (Science of The Total Environment, 2024)

Response of GFRP suction bucket in clay during installation - Hai-lei Kou; Zhao-tun An; Yong-kang Wang; Hong-rui Zhang; Xi-xin Zhang (Ocean Engineering, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Triboelectric nanogenerator based on multi-component crosslinked network hydrogel for intelligent human motion sensing - Kang-Rui Zhu; Lin-Xin Wu; Meng-Nan Liu; Chang-Long Li; Wei-Zhi Song; Kong-Qiang Wei; Jun Zhang; Seeram Ramakrishna; Yun-Ze Long (Chemical Engineering Journal, 2024)

Recovery hydrotalcite from neutralization sludge of acid mine drainage with high manganese for degradation of norfloxacin with activated peroxymonosulfate - Qingsheng Xu; Zhengbo Yue; Rui Deng; Kang Su; Xin Chuai; Kai Zhang; Jin Wang (Chemical Engineering Journal, 2024)

Transport properties of oil-CO2 mixtures in calcite nanopores: Physics and machine learning models - Hongwei Zhang; Xin Wang; Qinjun Kang; Bicheng Yan; Shuyu Sun; Rui Qiao (Fuel, 2024)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Effects of microplastics on functional genes related to CH4 and N2O metabolism in bacteriophages during manure composting and its planting applications - Wei-Kang Deng; Jun-Liang He; Jing-Yuan Chen; Rui-Ting Wu; Si-Cheng Xing; Xin-Di Liao (Journal of Hazardous Materials, 2023)

Association between PM2.5 exposure and the outcomes of ART treatment: A prospective birth cohort study - Yifan Wang; Yun Qiu; Bo Huang; Jiangbo Du; Liya Liu; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; et al. (Science of The Total Environment, 2023)

Moringa oleifera Lam. leaves as new raw food material: A review of its nutritional composition, functional properties, and comprehensive application - Min Yang; Liang Tao; Xin-Rui Kang; Zi-Lin Wang; Ling-Yan Su; Ling-Fei Li; Fan Gu; Cun-Chao Zhao; Jun Sheng; Yang Tian (Trends in Food Science & Technology, 2023)

mRNA 3ʹ -UTR-mediate translational control through PAS and CPE in sheep oocyte - Chun-Ru Song; Ru-Jing Zhang; Fang-Rui Xue; Xiao-Jie Zhang; Xing-Yue Wang; Dui Sun; Kang Ding; Qi Yang; Xin-Yu Wang; Cheng-Guang Liang (Theriogenology, 2023)

High density mapping of wheat stripe rust resistance gene QYrXN3517-1BL using QTL mapping, BSE-Seq and candidate gene analysis - Shuo Huang; Yibo Zhang; Hui Ren; Xin Zhang; Rui Yu; Shengjie Liu; Qingdong Zeng; Qilin Wang; Fengping Yuan; Ravi P. Singh; Sridhar Bhavani; Jianhui Wu; et al. (Theoretical and Applied Genetics, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Receptor and Ionic Mechanism of Histamine on Mouse Dorsolateral Striatal Neurons - Jian-Ya Peng; Kang-Li Shen; Xiu-Juan Fan; Zeng-Xin Qi; Hui-Wei Huang; Jian-Lan Jiang; Jian-Hua Lu; Xiao-Qin Wang; Xiao-Xia Fang; Wang-Rui Yuan; Qiao-Xuan Deng; Shu Chen; et al. (Molecular Neurobiology, 2023)

Genistein Alleviates Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus by Activating the Sirt1/Nrf2 Pathway in High Salt-Induced Hypertension - Li-Gang Niu; Na Sun; Kai-Li Liu; Qing Su; Jie Qi; Li-Yan Fu; Guo-Rui Xin; Yu-Ming Kang (Cardiovascular Toxicology, 2022)

Identification of Ferroptotic Genes in Spinal Cord Injury at Different Time Points: Bioinformatics and Experimental Validation - Yu Kang; Qiangwei Li; Rui Zhu; Shuang Li; Xin Xu; Xuanming Shi; Zongsheng Yin (Molecular Neurobiology, 2022)

High-Frequency Repetitive Transcranial Magnetic Stimulation Regulates Astrocyte Activation by Modulating the Endocannabinoid System in Parkinson’s Disease - Xin Kang; Bing Zhang; Wanqing Du; Rui Zhao; Xuedong Liu; Ya Bai; Xiaobing Jiang; Jie Pang; Chenguang Zhao; Xiang Mou; Fang Gao; Hua Yuan; et al. (Molecular Neurobiology, 2022)

Carbon Monoxide Attenuates High Salt-Induced Hypertension While Reducing Pro-inflammatory Cytokines and Oxidative Stress in the Paraventricular Nucleus - Dong-Dong Zhang; Yan-Feng Liang; Jie Qi; Kai B. Kang; Xiao-Jing Yu; Hong-Li Gao; Kai-Li Liu; Yan-Mei Chen; Xiao-Lian Shi; Guo-Rui Xin; Li-Yan Fu; Yu-Ming Kang; et al. (Cardiovascular Toxicology, 2019)

Effect of grazing on the abundance of functional genes associated with N cycling in three types of grassland in Inner Mongolia - K. Ding; L. Zhong; X. P. Xin; Z. H. Xu; X. M. Kang; W. J. Liu; Y. C. Rui; L. L. Jiang; L. Tang; Y. F. Wang (Journal of Soils and Sediments, 2015)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)